A mechanical study on the mitigation of lodging in edible canna - Katsu Imai; Ryosuke Kiya (Plant Production Science, 2017)
Because edible canna is approximately 3-m tall in its latter growth stage, strong winds such as by typhoons can induce plant lodging and cause severe damage to it. To improve our previous estimations that the 1-m dwarfing of a plant mitigated 10–20% by strong wind (external force) and 50% by own weight (internal force), respectively, we re-examined these parameters in relation to rhizome yield for field-grown plants. From early middle growth stage (July–August) of edible canna, the perpendicularly projected area of above-ground biomass increased rapidly due to rapid shoot elongation. After the middle growth stage (September), the stock base radius increased and shoot inclination angle decreased until the latter growth stage (November) gradually, indicating a disturbed architecture and easy lodging. Throughout the growth period, we observed no radial, directional difference in the leaf area distribution. Increase in the distance between the ground surface and the center of gravity of shoot weight and decrease in the shoot inclination increased the components of the internal force. The easiness to fall down (percentage own-weight invasion moment) of plant became maximal in the latter growth stage. We conclude that approximately 50-cm dwarfing of the plant with minimal loss of rhizome yield (as low as approximately 20%) and the maintenance of lodging tolerance is optimal. In such a situation, both external and internal forces are mitigated by approximately 30%.